Assessment of dental implant site dimensions in cone beam computed tomography systems - Shokri, Abbas; Khajeh, Samira; Falah-kooshki, Sepideh; Ostovarrad, Farzaneh; Karimi, Atena; Khavid, Atefeh (Brazilian Dental Science, 2014)
Objective: The aim was to investigate the accuracy of linear measurements the mandibular ridge recorded using two CBCT systems. Materials and Methods: Eleven human dry skull were used in which mandibles were chosen to measure width and height in 6 sites. Before scanning, the points were marked using barium sulfate radiopaque contrast media. Mandible imaging was done using two systems: Newtom3G and Cranex3D. Alveolar ridge dimensions were recorded by two observers under uniform condition using special software for each system. The measurement errors and inter-examiner reliability were calculated for each modality and compared with each other and analyzed via SPSS software version 18. The level of significance was set at P< 0.05. Results: The overall mean absolute error was 0.08 mm for Cranex system and 0.5 for Newtom system. The mean absolute error of two systems had no statistically significant difference in comparison with each other or with the gold standard. The statistical analysis showed high inter-observer reliability (P < 0.05). Conclusion: CBCT is highly accurate and reproducible in linear measurements in the axial and coronal images planes and in different areas of the maxillofacial region.Keywords: Barium sulfate; Cranex3D; Cone beam computed tomography; Dental implant; Newtom3G.